Colonoscopy-related adverse events and mortality in an Italian organized colorectal cancer screening program - Benazzato, Luca; Zorzi, Manuel; Antonelli, Giulio; Guzzinati, Stefano; Hassan, Cesare; Fantin, Alberto; and the Veneto Screening Endoscopists Working Group (Endoscopy, 2020)
Background Post-colonoscopy adverse events are a key quality indicator in population-based colorectal cancer screening programs, and affect safety and costs. This study aimed to assess colonoscopy-related adverse events and mortality in a screening setting.Methods We retrieved data from patients undergoing colonoscopy within a screening program (fecal immunochemical test every 2 years, 50–69-year-olds, or post-polypectomy surveillance) in Italy between 2002 and 2014, to assess the rate of post-colonoscopy adverse events and mortality. Any admission within 30 days of screening colonoscopy was reviewed to capture possible events. Mortality registries were also matched with endoscopy databases to investigate 30-day post-colonoscopy mortality. Association of each outcome with patient-/procedure-related variables was assessed using multivariable analysis.Results Overall, 117 881 screening colonoscopies (66 584, 56.5 %, with polypectomy) were included. Overall, 497 (0.42 %) post-colonoscopy adverse events occurred: 281 (0.24 %) bleedings (3.69‰/0.68‰, operative/diagnostic procedures) and 65 (0.06 %) perforations (0.75‰/0.29‰, respectively). At multivariable analysis, bleeding was associated with polyp size (≥ 20 mm: odds ratio [OR] 16.29, 95 % confidence interval [CI] 9.38–28.29), proximal location (OR 1.46, 95 %CI 1.14–1.87), and histology severity (high risk adenoma: OR 5.6, 95 %CI 2.43–12.91), while perforation was associated with endoscopic resection (OR 2.91, 95 %CI 1.62–5.22), polyp size (OR 4.34, 95 %CI 1.46–12.92), and proximal location (OR 1.94, 95 %CI 1.12–3.37). Post-colonoscopy mortality occurred in 15 /117 881 cases (1.27/10 000 colonoscopies).Conclusions In an organized screening program, post-colonoscopy adverse events were rare but not negligible. The most frequent event was post-polypectomy bleeding, especially after resection of large (≥ 20 mm) and proximal lesions.